RESPON PERTUMBUHAN STEK BATANG ANGGREK Dendrobium secundum (BI.) Lindl. PADA KOMBINASI KONSENTRASI DAN INTENSITAS PEMBERIAN ZAT PENGATUR TUMBUH - Zulkaidhah, Zulkaidhah; Wardah, Wardah; Adnyani, Dewa Ayu (Universitas Tadulako, 2019)
Dendrobium orchid has great potential to be developed. The problem faced in its development is the decrease of orchid productivity per square meter of cultivation area. Consequently, the less availability of orchid either in quality and quantity. Whereas, there are growth regulator substances might be used to fulfill the hormone needs of orchid to obtain optimal growth. The main constraint is how the growth regulator substance in a certain amount affected the dendrobium archid growth. The research objective is to assess the growth response of stem cuttings of Dendrobium secundum orchid in combination of concentration and application intensity of growth regulator. This research was conducted for 3 months from October to January 2018, at Orchid Green House of the Permanent Nursery of BPDAS Palu Poso, Tadulako University. The results of study showed that the best treatment was combination of NAA (1 ml) + BAP (1 ml)/liter of water applied once a week (P1), which gave the fastest shoot growth of 16.25 days and had the highest growth on the shoot height of 3.5 cm and on the leave number of 4 sheets at the age of 12 weeks after planting.